Hepatic vascular inflow occlusion is associated with reduced disease free survival following resection of colorectal liver metastases. Issue 1 (January 2017) - Olthof, P.B.; Huiskens, J.; Schulte, N.R.; Wicherts, D.A.; Besselink, M.G.; Busch, O.R.C.; Tanis, P.J.; van Gulik, T.M.
Abstract: Background: Hepatic vascular inflow occlusion (VIO) can be applied during resection of colorectal liver metastases (CRLM) to control intra-operative blood loss, but has been linked to accelerated growth of micrometastases in experimental models. This study aimed to investigate the effects of hepatic VIO on disease-free and overall survival (DFS and OS) in patients following resection for CRLM. Methods: All patients who underwent liver resection for CRLM between January 2006 and September 2015 at our center were analyzed. Hepatic VIO was performed if deemed indicated by the operating surgeon and severe ischemia was defined as ≥20 min continuous or ≥45 min cumulative intermittent VIO. Cox regression analysis was performed to identify predictive factors for DFS and OS. Results: A total of 208 patients underwent liver resection for CRLM. VIO was performed in 64 procedures (31%), and fulfilled the definition of severe ischemia in 40 patients. Patients with severe ischemia had inferior DFS (5-year DFS 32% vs. 11%, P < 0.01), and inferior OS (5-year OS 37% vs. 64%, P < 0.01). At multivariate analysis, a high clinical risk score (Hazard ratio (HR) 1.60 (1.08–2.36)) and severe ischemia (HR 1.89 (1.21–2.97)) were independent predictors of worse DFS. Severe ischemia was not an independent predictor of OS. Conclusion: The present cohort study suggests that prolonged hepatic VIO during liver resection for CRLM was associated with reduced DFS. A patient-tailored approach seems advisable although larger studies should confirm these findings.